Strength training for children and adolescents: Benefits and risks - Barbieri, D.; Zaccagni, L. (Collegium Antropologicum, 2013)
Physical activity has proved to be an effective means of preventing several diseases and improving general health. In most cases, though, light to moderate efforts are suggested, for both youngsters and adults. Common sense advices call for late inception of intense, strength training-related activities, like weight lifting and plyometrics, which are usually postponed at the end of the growth age, even among sport practitioners. However, such advices seem to have a mainly anecdotal nature. The purpose of this review is to evaluate risks and benefits of early inception of strength training, at adolescence or even earlier, and to verify whether concerns can be grounded scientifically. Current literature does not seem to have any particular aversion against the practice of strength training by children and adolescents, provided that some safety rules are followed, like medical clearance, proper instruction from a qualified professional and progressive overload. At the same time, several studies provide consistent findings supporting the benefits of repeated, intense physical efforts in young subjects. Improved motor skills and body composition, in terms of increased fat free mass, reduced fat mass and enhanced bone health, have been extensively documented, especially if sport practice began early, when the subjects were pubescent. It can be therefore concluded that strength training is a relatively safe and healthy practice for children and adolescents.